Aβ degradation or cerebral perfusion? Divergent effects of multifunctional enzymes - Miners, J. Scott; Palmer, Jennifer C.; Tayler, Hannah; Palmer, Laura E.; Ashby, Emma; Kehoe, Patrick G.; Love, Seth (Frontiers in Aging Neuroscience, 2014)
There is increasing evidence that deficient clearance of β-amyloid (Aβ) contributes to its accumulation in late-onset Alzheimer disease (AD). Several Aβ-degrading enzymes, including neprilysin (NEP), endothelin-converting enzyme (ECE) and angiotensin-converting enzyme (ACE) reduce Aβ levels and protect against cognitive impairment in mouse models of AD. In post-mortem human brain tissue we have found that the activity of these Aβ-degrading enzymes rise with age and increases still further in AD, perhaps as a physiological response that helps to minimize the build-up of Aβ. ECE-1/-2 and ACE are also rate-limiting enzymes in the production of endothelin-1 (ET-1) and angiotensin II (Ang II), two potent vasoconstrictors, increases in the levels of which are likely to contribute to reduced blood flow in AD. This review considers the possible interdependence between Aβ-degrading enzymes, ischemia and Aβ in AD: ischemia has been shown to increase Aβ production both in vitro and in vivo, whereas increased Aβ probably enhances ischemia by vasoconstriction, mediated at least in part by increased ECE and ACE activity. In contrast, NEP activity may help to maintain cerebral perfusion, by reducing the accumulation of Aβ in cerebral blood vessels and lessening its toxicity to vascular smooth muscle cells. In assessing the role of Aβ-degrading proteases in the pathogenesis of AD and, particularly, their potential as therapeutic agents, it is important to bear in mind the multifunctional nature of these enzymes and to consider their effects on other substrates and pathways.